(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2022)
The banana production in the north of Minas Gerais state is based on the “Prata-Anã” cultivar, holding 90% of the 10,000 hectares cultivated with the species. Such cultivar is vulnerable to Yellow and Black Sigatoka, as well as to the Panama disease. A strategy to overcome these phytosanitary problems is the development of resistant cultivars, which need field testing. This study aimed to determine the yield and the nutritional diagnosis for N and K of banana tree cultivars FHIA 1, FHIA 2, FHIA 3, Pacovan Ken, Thap Maeo, Tropical, Caipira, ST406, PV4285, and PV4253, resistant to Yellow Sigatoka. Also, Prata anã, a disease-sensitive cultivar, was used as a control treatment. According to the results, the FHIA 3 produced bunches with more mass, standing out among cultivars of the tetraploid genomic group. However, complimentary assessment is necessary to be suggested as a cultivar in the commercial crops, mainly the acceptability of its fruits by consumers. FHIA 2 has also produced bunches with meaningful mass, being an alternative to bananas of the Cavendish subgroup due to the similar taste. Thap Maeo, among the triploid cultivars, reached a high yield, being an alternative to the cultivation of the apple banana tree, as it is resistant to Yellow and Black Sigatoka and the Panama disease in addition to producing fruits of adequate taste. The N and K contents were in the sufficiency range, revealing that in such environmental conditions, plants were sufficiently nourished.